THE INFLUENCE OF COMPENSATION, WORKING ENVIRONMENT, AND WORK DISCIPLINE ON EMPLOYEE Performance (Empirical Study at Semarang City Health Office) - Ditha Ersa Melani; Sri Isnowati (SEAN Institute, 2023)
This study aims to determine and explain the effect of compensation, work environment, and work discipline on employee performance at the Semarang City Health Office. This study used primary data and sampling techniques using a purposive sampling method obtained through a questionnaire/questionnaire by distributing 100 Semarang City Health Office employees as the research sample. The tests carried out in this study included validity tests, reliability tests, model tests, t tests and F tests. The results of this study indicate that partially and simultaneously the compensation, work environment, and work discipline variables affect employee performance